KEUNGGULAN SISTEM E-BUSINESS DALAM PERSAINGAN BISNIS - Maylin Azzahra; Ardina Khoirunisa H; Hamzah Muhammad; Nurbaiti (Journal of Innovation Research and Knowledge, 2021)
This research focuses on the increasingly sophisticated technology from time to time, so that the business environment is also increasingly competitive. At this time technology is needed in every activity of the organization. E-business itself means the use of technology and also information systems that manage business from manual to automatic in order to accelerate the availability of information needed to reach decisions. By using E-business can make the process faster. Even today, it is not only marketing products that use technology, every transaction uses technology. Or even in selling their products using Electronic such as E-commerce, and even in terms of payment also using technology such as E-money. But the implementation of E-business itself has advantages and disadvantages. The drawback is that the network can be lost, there can also be technical errors, can't see the goods directly, can only see the goods through photos and customer reviews. Meanwhile, the advantages of E-business are that there is no need to rent a physical store, product marketing is also easier, increasing sales and can also save time. However, with E-business we can see great opportunities especially in our current new normal era.